"Mutiara Ramadhan" Da’wah Program at RRI Bengkulu: A Review of the Theory of the Hierarchy of Media Content Influence - Destiana, Destiana; Musyaffa, Musyaffa; Alfandi, Muhammad (Jurnal Ilmiah Syi'ar, 2024)
This research aims to describe the hierarchy of influence of da'wah messages broadcast by the Public Broadcasting Institution (LPP) Radio Republik Indonesia (RRI) Bengkulu. This research reviews how the structure of delivering the content of da'wah messages and the dominant hierarchical factors have an influence on the Mutiara Ramadhan program. This research used a descriptive-qualitative approach. Researchers interviewed key informants, in-depth interviews with broadcasters and program performers to obtain a more comprehensive perspective. Researchers made observations of the Mutiara Ramadhan program, and analyzed documents on the content that had been broadcast.  As an analytical tool, this research used the hierarchy of influence theory to examine the influence of da'wah messages. The research had resulted show that two main factors in the Hierarchy of Media Content Influence review influence the existence of the Mutiara Ramadhan program.  Internal media factors, aspects of workers (individuals) who are Muslim, are used to Islamic broadcasting programs during Ramadan, and the routine every time during Ramadhan is to always present Islamic broadcasting programs (Media Routine). As for external media factors, such as organizational structure, through policies, policy makers encourage the Mutiara Ramadhan program. Apart from that, at the media institutional level, considering that RRI Bengkulu's loyal listening audience is predominantly Muslim, the total population of 98% of the Muslim population is taken into consideration. Then, the level of Social System or Ideology is shown by the entire leadership structure being Muslim, and the majority of workers being Muslim, so there is an interest in maintaining their ideological beliefs.